Beginning LEGO MINDSTORMS EV3 - Rollins, Mark.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2014)
Beginning LEGO MINDSTORMS EV3 shows you how to create new fun and fantastic creations with the new EV3 programmable brick along with other new EV3 pieces and features. You'll learn the language of the EV3 brick, and then go on to create a variety of programmable vehicles using MINDSTORMS and Technic parts. You'll then move into creating robot parts, including robotic arms. You'll even learn how to make different types of MINDSTORMS walkers. Finally, you'll learn how to incorporate light and sound into your amazing EV3 creations. Whether you're a MINDSTORMS enthusiast wanting to know more about EV3, a robotics competitor, or just a LEGO fan who wants to learn all about what EV3 can do, Beginning LEGO MINDSTORMS EV3 will give you the knowledge you need. Note: the printed book is in black and white. The Kindle and ebook versions are in color (black and white on black and white Kindles).
Keywords: Computer input-output equipment; Computer hardware; Hardware and Maker; Computer Hardware